2009
DOI: 10.1038/eye.2009.95
|View full text |Cite
|
Sign up to set email alerts
|

Performance of GDx and HRT in the Finnish Evidence-Based Guideline for Open-Angle Glaucoma

Abstract: Aim To compare the performance of Heidelberg retina tomograph (HRT) and scanning laser polarimetry (GDx) with photographic evaluation of the optic nerve head (ONH) and retinal nerve fiber layer (RNFL) in the application of the Finnish Evidence-Based Guideline for Open-Angle Glaucoma. Methods A total of 41 control participants and 312 patients referred for glaucoma evaluation were included in the study. All the participants underwent ophthalmic evaluation, ONH stereophotography, monochromatic RNFL photography, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Similar to other studies (7, 8), the participants were not selected by applying a gold standard glaucoma test. Because glaucoma cannot be defined outside the context of structure and function, and both structure and function were being evaluated in this study, the use of a structural or functional gold standard could induce a bias.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other studies (7, 8), the participants were not selected by applying a gold standard glaucoma test. Because glaucoma cannot be defined outside the context of structure and function, and both structure and function were being evaluated in this study, the use of a structural or functional gold standard could induce a bias.…”
Section: Methodsmentioning
confidence: 99%
“…Application of the FEBG-OAG classifies the subjects into several groups, including those with normal findings, and several groups with suspected glaucoma or glaucoma. Similar to other studies (7,8), the participants were not selected by applying a gold standard glaucoma test. Because glaucoma cannot be defined outside the context of structure and function, and both structure and function ommendations for glaucoma management, such as the European Glaucoma Society Guidelines, the American Academy of Ophthalmology Preferred Practice Patterns for Open-Angle Glaucoma, and the Finnish Evidence-Based Guideline for Open-Angle Glaucoma (FEBG-OAG) (4)(5)(6).…”
Section: Study Groupsmentioning
confidence: 99%
“…The latest method, called enhanced corneal compensation (ECC), is said to have further improved the evaluation of the RNFL by the SLP device and, according to recent studies [4, 5] has increased both the diagnostic accuracy and the correlation between functional and structural measurements. Recent research indicates that there is still a large gap between the diagnostic conclusions reached using these modern imaging devices and the clinical assessment: a study of 312 glaucoma patients and 41 control participants by Pablo et al ., [6] found that the agreement between the stereophotographic evaluations and the conclusions based on SLT and SLP was just 52.9%. Medeiros et al, [7] could show already SLP with VCC to be superior to these techniques, and that the new SLP ECC technology again is an advantage in image quality and provides an increased ability to detect early glaucomatous damage and even small changes [8].…”
Section: Introductionmentioning
confidence: 99%